Alasan Iran Memblokir Konsensus Dalam Sidang Arms Trade Treaty Tahun 2013 - Desrsal, Nanda Sidni (Global and Policy Journal of International Relations, 2019)
ABSTRACTThe purpose of this paper is to explain the importance of Iran which is the main reason for blocking consensus in the Arms Trade Treaty session held in 2013. Meanwhile, the object of this research leads to the activities of transferring Iranian weapons to terrorist groups such as Hezbollah, Hamas, and Palestinian Islamic Jihad making Iran block consensus in the Arms Trade Treaty session held in 2013. This research is a qualitative-explanative research supported by accurate data sources, both primary through official sites that are related and secondary through books, scientific journals, online articles, and other references. Then the explanative explanation of causality, in this study explains the reason Iran blocked consensus at the 2013 Arms Trade Treaty session because Iran had an interest in dealing with the proposal of the Arms Trade Treaty agreement. The results showed that in the same year when Iran did not report the results of its weapons exports to the United Nations, Iran exported weapons to terrorist groups. This was proven through statements issued through representatives of both parties and weapons evidence found. So that illegal weapons transfer activities made Iran block consensus because the contents of the Arms Trade Treaty proposal that explained the prohibition of arms transfers for matters that violate international provisions and related to terrorism, genocide, transnational crime.Keywords: Arms Trade Treaty, Iran, Illegal Arms Transfer DOI : https://doi.org/10.33005/jgp.v7i02.1831